Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1089/jmf.2017.3994
|View full text |Cite
|
Sign up to set email alerts
|

Sea Cucumber Lipid-Soluble Extra Fraction Prevents Ovalbumin-Induced Allergic Airway Inflammation

Abstract: In a previous study, our research group demonstrated that sea cucumber (Apostichopus japonicus) extracts ameliorated allergic airway inflammation through CD4CD25Foxp3 T (regulatory T; Treg) cell activation and recruitment to the lung. In this study, we aimed to determine which components of sea cucumber contribute to the amelioration of airway inflammation. We used n-hexane fractionation to separate sea cucumber into three phases (n-hexane, alcohol, and solid) and evaluated the ability of each phase to elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Interleukin (IL)-10 gene expression level were significantly affected by different experimental diets fed sea cucumbers extract. IL-10 is an antiinflammatory cytokine, secreted by Treg cells, suppress immune responses and also can inhibit the synthesis of pro--inflammatory cytokines, protect against asthma disease [47]. In the present study, we found that (IL)-10 gene expression level significantly increased in the spleen of mice induced by 10 and 15% Saccharina japonica diets fed sea cucumbers extracts.…”
Section: Discussionsupporting
confidence: 55%
“…Interleukin (IL)-10 gene expression level were significantly affected by different experimental diets fed sea cucumbers extract. IL-10 is an antiinflammatory cytokine, secreted by Treg cells, suppress immune responses and also can inhibit the synthesis of pro--inflammatory cytokines, protect against asthma disease [47]. In the present study, we found that (IL)-10 gene expression level significantly increased in the spleen of mice induced by 10 and 15% Saccharina japonica diets fed sea cucumbers extracts.…”
Section: Discussionsupporting
confidence: 55%
“…A component of this extract, n-hexane, a fatty-acid-rich fraction, ameliorated allergic airway inflammation in a mouse model of ovalbumin-induced asthma: eosinophil infiltration and goblet cell hyperplasia were significantly reduced around the airways, and the concentrations of Th2-related cytokines (IL-4, IL-5, and IL-13) and Th17-related cytokines (IL-17) were significantly decreased in the spleen and bronchoalveolar lavage fluid [88].…”
Section: Cytokine Levels 421 Th2 Cytokinesmentioning
confidence: 99%
“…Experimental studies with marine compounds demonstrating their effectiveness in in vitro or in vivo models of bronchial asthma are scarce [84][85][86][87][88]. On the other hand, recent studies revealed the significant potential of marine compounds to interfere with molecular mechanisms similar to those involved in GC-resistant asthma.…”
Section: Potentially Therapeutic Effect Of Marine-derived Biologically Active Compounds In Severe Asthmamentioning
confidence: 99%
“…Lee et al [ 59 ] investigated the anti-allergic activity of sea cucumber and demonstrated that the liquid salting-out extract of sea cucumber activated and recruited regulatory T and Treg cells that improved allergic airway inflammation. Moreover, sea cucumber extract rich in palmitoleic acid inhibited IgE better than extracts poor in palmitoleic acid, whereas palmitoleic acid lowers serum total immunoglobulin E (IgE) concentrations.…”
Section: Chemical Structures and Biological Properties Of The Anti-al...mentioning
confidence: 99%